The Development Strategy of Foreign Trade Settlements by Letter of Credit Method - Laukaitis, Ričardas (Ekonomika, 2000)
The article investigates the problems, which impede the development of foreign trade settlements by letter of credits, and describes the means, which can decrease those problems effect. The letters of credits can decrease the risk involved in foreign trade operation and granting of loans to trade companies, hut from other point of view they can decrease the company’s profitability and liquidity. We propose to implement innovations to Lithuanian banking sector, which can more effectively solve those problems. It is proposed to use factoring and foreign trade financial resources in financing Lithuanian exporters involved in letter of credit transactions. Also we propose to Lithuanian banks to rationalise the fees of letters of credits. use this settlement method for management loan risk and promote it among Lithuanian companies. It is recommended to Lithuanian companies to settle foreign trade account by letter of credit trough foreign hank branches in Lithuania.